HAK WARIS ANAK DI lUAR NIKAH PERSPEKTIF HUKUM ISlAM DAN HUKUM POSITIF - Lena Ananda; Dwi Ari Kurniawati; Moh Muslim (Jurnal Hikmatina, 2020)
Abstract            In essence, children born out of wedlock usual ly get the nickname of adultery or illegitimate chilldren. and thus can cause psychological disturbances against the child, although legally the child also has legal consequences from the actions carried out by both parents. But there are some problems for people who are pregnant outnofgwedlocknincluding the termination of nasab for the child to his biological father and the termination of the inheritancenofochildrennbornkoutnof wedlock. with regard to children outside ofnmarriage canobenseenfromnthe position ofnchildren born out ofowedlock itself. whereas in Islamic law and positive law there is a rule that a child out of wedlock is entitled to his rights, for example his right otonin her it ufromo his biological fathernby means of his biological mother and father engaging in legal marriage according to religion and the State, there will be there is an inheritance right from his biological father in the form of compulsory testament that is equal to l/3 of his assets, and as biological father must meet the needs and rights of the child.Keywords: inheritance right of children, Islamic law, positive legal.